Mowing detection intercomparison exercise (MODCiX) – Evaluation of grassland mowing detection algorithms across Europe - Marcel Schwieder; Felix Lobert; Dominique Weber; Sophie Reinermann; Sarah Asam; Filippo Sarvia; Samuele De Petris; Enrico Borgogno-Mondino; Arnab Muhuri; Natascha Oppelt; Clement Atzberger; Iason Tsardanidis; et al. (Remote Sensing of Environment, 2026)

How landscape factors relate to biodiversity-economic performance in an Estonian grassland-rich region - Takamasa Nishizawa; Johannes Schuler; Miguel Villoslada; Claudia Bethwell; Michael Glemnitz; Maaria Semm; Monika Suškevičs; Kalev Sepp; Rando Värnik; Florian Kestel; Meelis Ots; Peter Zander; et al. (Environmental Management, 2026)
Halting biodiversity loss on semi-natural grassland has become a key priority of agri-environmental policies in Estonia. However, to what extent current schemes are sufficient to achieve biodiversity targets and the role of landscape factors is still insufficiently understood in this context. This study explored trade-offs between profitability and biodiversity conservation across heterogeneous Estonian agricultural landscapes to support the development of economically effective grassland conservation schemes. To this end, we selected twelve ‘landscape windows’ in a grassland-rich region that represent a gradient of several biodiversity-related landscape factors (semi-natural grassland share, yield potential and landscape complexity). Profitability was assessed using total gross margins derived from a bio-economic model, while biodiversity was evaluated through habitat values for different bird species, based on model outputs. We found that landscapes with higher complexity, which currently maintain higher biodiversity levels, had a corresponding lower farm profitability. In particular, landscape windows dominated by semi-natural grasslands with low grass yields showed the lowest profitability, largely due to limited capacity for feeding beef cattle. In contrast, arable land-dominated landscapes (i.e. those with higher yield potential) demonstrated considerable potential for enhancing biodiversity outcomes while minimising profitability losses. Therefore, conservation policy faces two main challenges: 1. preserving landscapes with high biodiversity value against further decline in profitability, 2. highlighting the need to explore and design biodiversity measures in arable-dominated landscapes that could improve biodiversity outcomes while limiting impacts on farm profitability. This study illustrates that landscape factors deserve greater attention in conservation planning.

School greenness and children's academic achievement and well-being: A population-wide study from Norway - Vidar Sandsaunet Ulset; Jørgen Tronsen; Emma Charlott Andersson Nordbø; Zander Venter (Environmental Research, 2026)

Metabolic Dynamics of Central Carbon Pathways in Green‐Lipped Mussels under Heat Stress and Subsequent Recovery - Leonie Venter; Andrea C. Alfaro; Jeremie Zander Lindeque; Peet J. Jansen van Rensburg; Norman L. C. Ragg; Jessica A. Ericson; Natalí J. Delorme (New Zealand Journal of Marine and Freshwater Research, 2026)
Green‐lipped mussel ( Perna canaliculus ) aquaculture is vulnerable to environmental changes, which are increasingly being studied to pinpoint physiological, economic and ecological threats. This study utilised a targeted liquid chromatography‐mass spectrometry metabolomics approach, focusing on the central carbon metabolism, to examine the metabolic response of P. canaliculus haemolymph to heat stress (30°C) and multi‐point recovery (up to 47 h). Heat stress disturbed sugar‐based‐, amino acid‐ and purine‐derived metabolites, implementing anaerobic pathways and phosphagen breakdown, following initial thermal exposure, to support energy production. Time course recovery revealed varying metabolic adjustments in P. canaliculus , resulting in new metabolic setpoints in the heat‐stressed mussel group, which overlapped with the responses of the control group. Metabolic recovery in metabolites, such as pyruvate and malate, suggests the gradual return to aerobic energy generation, while amino acids, such citrulline, methionine and tyrosine, supported protein regulation and nitrogen homeostasis. In addition, purine‐derived metabolites (guanosine diphosphate, guanosine and guanine) linked to guanine‐based nucleotides support the use thereof towards energy production in heat‐stressed mussels, after which their levels stabilised, to control levels. Overall, the results show that P. canaliculus implements specific metabolic adjustments, as shifts in energy‐related and stress‐associated metabolites, to cope with short‐term high‐temperature exposure. After around two days of recovery at ambient temperatures, these metabolites do not simply return to baseline but instead stabilise at a new metabolic setpoint, suggesting a reprogramming of physiological homeostasis. These changes reflect an adaptive response in mussels that provides valuable insight for climate change adaptation and breeding resilient stocks.

Impacts of forest clear-cutting on recreational activity: Evidence from crowdsourced mobility data - Zander S. Venter; David N. Barton; Vegard Gundersen (Landscape and Urban Planning, 2025)

Assessing recreationists’ preferences of the landscape and species using crowdsourced images and machine learning - Abdesslam Chai-allah; Johannes Hermes; Anne De La Foye; Zander S. Venter; Frédéric Joly; Gilles Brunschwig; Sandro Bimonte; Nathan Fox (Landscape and Urban Planning, 2025)

The metabolic fate of abalone: transport and recovery of Haliotis iris gills as a case study - Leonie Venter; Andrea C. Alfaro; Jeremie Zander Lindeque; Peet J. Jansen van Rensburg (New Zealand Journal of Marine and Freshwater Research, 2025)
Abalone is a gourmet seafood with a high commercial value, particularly when obtained as a live product. During live transportation, abalone encounter stressors causing biochemical modifications to tolerate the changes. Using semi‐targeted metabolomics, this study characterised the left and right gill metabolite profiles of Blackfoot abalone, Haliotis iris , following transportation (48 h) and recovery (48 h). This study reports the association between left and right gill metabolites, to enhance our physiological understanding of the interplay between gills. The left gill metabolites are mainly active following transportation, while both gills partake in the metabolite response following recovery. Transportation necessitated increased metabolites linked to the glycolysis pathway, the Krebs cycle, amino acid, and nucleotide metabolism, for energy production, achieved via aerobic and anaerobic pathways. The recovery phase supported the replenishing of glycogen, triglycerides, and protein stores, albeit metabolic homeostasis was not achieved following two‐days of water immersion recovery. This study showcases the well‐adapted metabolic mechanisms implemented by H. iris in response to transportation stress and show that metabolites are in the process of returning to the same concentrations as measured pre‐transport stress. The findings herein can be applied to improve animal health during transport and subsequent survival, which in‐effect supports profitability.

‘Uncertainty audit’ for ecosystem accounting: Satellite-based ecosystem extent is biased without design-based area estimation and accuracy assessment - Zander S. Venter; Bálint Czúcz; Erik Stange; Megan S. Nowell; Trond Simensen; Bart Immerzeel; David N. Barton (Ecosystem Services, 2024)

Bias and precision of crowdsourced recreational activity data from Strava - Zander S. Venter; Vegard Gundersen; Samantha L. Scott; David N. Barton (Landscape and Urban Planning, 2023)

Environmental justice in a very green city: Spatial inequality in exposure to urban nature, air pollution and heat in Oslo, Norway - Zander S. Venter; Helene Figari; Olve Krange; Vegard Gundersen (Science of The Total Environment, 2023)

The importance of Indigenous Peoples’ lands for the conservation of terrestrial mammals - Christopher J. O'Bryan; Stephen T. Garnett; Julia E. Fa; Ian Leiper; Jose A. Rehbein; Álvaro Fernández‐Llamazares; Micha V. Jackson; Harry D. Jonas; Eduardo S. Brondizio; Neil D. Burgess; Catherine J. Robinson; Kerstin K. Zander; et al. (Conservation Biology, 2021)
Indigenous Peoples’ lands cover over one‐quarter of Earth's surface, a significant proportion of which is still free from industrial‐level human impacts. As a result, Indigenous Peoples and their lands are crucial for the long‐term persistence of Earth's biodiversity and ecosystem services. Yet, information on species composition on these lands globally remains largely unknown. We conducted the first comprehensive analysis of terrestrial mammal composition across mapped Indigenous lands based on data on area of habitat (AOH) for 4460 mammal species assessed by the International Union for Conservation of Nature. We overlaid each species’ AOH on a current map of Indigenous lands and found that 2695 species (60% of assessed mammals) had ≥10% of their ranges on Indigenous Peoples’ lands and 1009 species (23%) had >50% of their ranges on these lands. For threatened species, 473 (47%) occurred on Indigenous lands with 26% having >50% of their habitat on these lands. We also found that 935 mammal species (131 categorized as threatened) had ≥ 10% of their range on Indigenous Peoples’ lands that had low human pressure. Our results show how important Indigenous Peoples’ lands are to the successful implementation of conservation and sustainable development agendas worldwide.

Metallothionein 1 Overexpression Does Not Protect Against Mitochondrial Disease Pathology in Ndufs4 Knockout Mice - Hayley Christy Miller; Roan Louw; Michelle Mereis; Gerda Venter; John-Drew Boshoff; Liesel Mienie; Mari van Reenen; Marianne Venter; Jeremie Zander Lindeque; Adán Domínguez-Martínez; Albert Quintana; Francois Hendrikus van der Westhuizen (Molecular Neurobiology, 2021)

Abalone growth and associated aspects: now from a metabolic perspective - Leonie Venter; Du Toit Loots; Andre Vosloo; Peet Jansen van Rensburg; Jeremie Zander Lindeque (Reviews in Aquaculture, 2018)
Worldwide, there are approximately 100 Haliotis species, more commonly known as abalone or ‘Paua’ in New Zealand, ‘Venus's‐ears’ in Greece, ‘Awabi’ in Japan, ‘Perlemoen’ in South Africa and ‘Ormers’ in Europe. Regardless of what they are called in any part of the world, a high monetary value is coupled to this animal, because it is largely considered a seafood delicacy. Subsequently, a great deal of research primarily focused on improving the health and growth rates of abalone were carried out to maximise productivity of the commercial farming efforts in various countries. In this review, we comprehensively describe the most recent available scientific literature on abalone biology, and those aspects related to the growth of this organism; more specifically, those factors related to the uptake and breakdown of metabolic products which ensures long‐term growth. We subsequently discuss this in terms of basic animal design, farming outcomes, feeding, cellular growth mechanisms and the unique metabolic processes that exist in these species. Using this information and the knowledge of the metabolic processes in other organisms, we additionally make a number of new hypotheses regarding how these metabolic processes may function in terms of abalone growth. Based on the information presented in this review, we also identify major research opportunities and gaps in the existing knowledge of abalone metabolism, which when elucidated may not only serve the purpose of better understanding these organisms growth but also could potentially lead to increased productivity of the abalone commercial farming sector.

Biodiversity and ecology of flower-associated actinomycetes in different flowering stages of Protea repens - Zander R. Human; Casparus J. Crous; Francois Roets; Stephanus N. Venter; Michael J. Wingfield; Z. Wilhelm de Beer (Antonie van Leeuwenhoek, 2018)